Y-5=m(x-6)form

Simple and best practice solution for Y-5=m(x-6)form equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y-5=m(x-6)form equation:


Simplifying
Y + -5 = m(x + -6) * form

Reorder the terms:
-5 + Y = m(x + -6) * form

Reorder the terms:
-5 + Y = m(-6 + x) * form

Reorder the terms for easier multiplication:
-5 + Y = m * fmor(-6 + x)

Multiply m * fmor
-5 + Y = fm2or(-6 + x)
-5 + Y = (-6 * fm2or + x * fm2or)
-5 + Y = (-6fm2or + fm2orx)

Solving
-5 + Y = -6fm2or + fm2orx

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + Y = -6fm2or + 5 + fm2orx

Combine like terms: -5 + 5 = 0
0 + Y = -6fm2or + 5 + fm2orx
Y = -6fm2or + 5 + fm2orx

Reorder the terms:
Y = 5 + -6fm2or + fm2orx

Simplifying
Y = 5 + -6fm2or + fm2orx

See similar equations:

| -18=-x-11 | | 8y+y^2=180 | | 8y+y^2=189 | | 0.54(6)+.06x=.18(24+x) | | f(4)=9x+7 | | -8+6x+4x=-98 | | 13x+1=9x+5 | | 3(c-63)=27 | | 5x-9+3x=87 | | f(5)=3x+x^2 | | (X-2)/10=(x-7)/5 | | X+325=520 | | f(x)=3x+x^2 | | 4x+10-2x=-10 | | 3(k+9)=72 | | -t+-6=-10 | | 32(x-1)+115x+10(x+2)=1607 | | -24=8(r+63) | | 43=2x+2x+7 | | 3/7x3 | | 3h+2=-4 | | -2x-2+5x=16 | | 4(b-73)+44=60 | | 7-3m=13-5m | | p=15x-1000 | | 20=5+3m | | -4x+9+6x=23 | | (3x)/5=6/1 | | 10-2b^2=-88 | | 3x+8+3x=68 | | -2(k+5)=-4 | | 4(x+10)-7x=-2(x-13) |

Equations solver categories